2021
DOI: 10.3390/molecules26113178
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Molecule Drug Design Based on Systems Biology Approaches and Deep Neural Network to Mitigate Human Skin Aging

Abstract: Human skin aging is affected by various biological signaling pathways, microenvironment factors and epigenetic regulations. With the increasing demand for cosmetics and pharmaceuticals to prevent or reverse skin aging year by year, designing multiple-molecule drugs for mitigating skin aging is indispensable. In this study, we developed strategies for systems medicine design based on systems biology methods and deep neural networks. We constructed the candidate genomewide genetic and epigenetic network (GWGEN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Various studies suggest the influence of genetic polymorphisms of the TNFA gene (responsible for TNF- expression) in various chronic diseases [28,29,30]. In another study, it was suggested that IL6 (the gene responsible for IL6 expression) is a biomarker of health status in the elderly [31]. A number of studies have confirmed the association of the IL6 gene with longevity and diseases associated with premature aging [32,33].…”
Section: Stress Inflammation and Skinmentioning
confidence: 99%
“…Various studies suggest the influence of genetic polymorphisms of the TNFA gene (responsible for TNF- expression) in various chronic diseases [28,29,30]. In another study, it was suggested that IL6 (the gene responsible for IL6 expression) is a biomarker of health status in the elderly [31]. A number of studies have confirmed the association of the IL6 gene with longevity and diseases associated with premature aging [32,33].…”
Section: Stress Inflammation and Skinmentioning
confidence: 99%
“…The nodes of the candidate GWGEN are divided into several groups: proteins, receptors, transcription factors (TFs), genes, miRNAs, and lncRNAs. Then, candidate GWGENs are pruned to real GWGENs of psoriasis and non-psoriasis in Figure 2 using their corresponding microarray data by system identification in Equations ( 1)- (20) to trim off false positives in candidate GWGEN. Here, we utilize the Akaike information criteria (AIC) [21] in Equations ( 21)-( 28) to perform the system order detection method to trim off the false-positive interactions and obtain real GWGENs of psoriasis and non-psoriasis.…”
Section: An Overview Of Systems Biology Approaches For the Study Of P...mentioning
confidence: 99%
“…The constraints in Equations ( 18)-( 20) ensure that the estimated post-transcriptional regulatory ability of miRNAs on genes, lncRNAs, and miRNAs is negative. Therefore, we can estimate the optimal vectors Θa , Θb , Θc , Θd of the protein interaction, gene, lncRNA, and miRNA regulation by solving the constrained least squares parameter estimation problems in Equations ( 17)- (20) with the MATLAB Optimization Toolbox, respectively.…”
Section: Using the System Identification Scheme And System Order Dete...mentioning
confidence: 99%
“…Combinations of these factors vary from individual to individual, warranting the exploration of AI in this area as a means for regaining homeostasis of the skin with specific interventions and therapeutics. For example, using a neural network system with a large database, Yeh et al processed information regarding protein-protein interaction, gene regulation, and human skin gene expression data to identify possible pathways and biomarkers of skin aging [46]. Using drug-target interaction data, they also proposed two drug treatments based on the identified biomarkers, one for young adulthood to middle age and another for middle age to old age [46].…”
Section: Application Of Artificial Intelligence In Skin Aging Managementmentioning
confidence: 99%